2021
DOI: 10.3390/ijms22094621
|View full text |Cite
|
Sign up to set email alerts
|

Antisense Oligonucleotide-Based Rescue of Aberrant Splicing Defects Caused by 15 Pathogenic Variants in ABCA4

Abstract: The discovery of novel intronic variants in the ABCA4 locus has contributed significantly to solving the missing heritability in Stargardt disease (STGD1). The increasing number of variants affecting pre-mRNA splicing makes ABCA4 a suitable candidate for antisense oligonucleotide (AON)-based splicing modulation therapies. In this study, AON-based splicing modulation was assessed for 15 recently described intronic variants (three near-exon and 12 deep-intronic variants). In total, 26 AONs were designed and test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 61 publications
0
25
0
Order By: Relevance
“…There is extensive pre-clinical and clinical research on the use of ssAONs to correct splicing defects in inherited retinal dystrophies [ 35–37 ]. For example, for Stargardt disease, ssAONs to correct intronic mutations which cause exon elongation or pseudoexons in the ATP-binding cassette transporter type 4 subfamily A, ABCA4 , transcript show promise when tested in various cell models including induced pluripotent stem cell (iPSCs)-derived photoreceptor precursor cells [ 38 , 39 ]. The ssAON, sepofarsen, is under clinical development as a treatment for Leber congenital amaurosis [ 40 ] and an exon skipping ssAON is being investigated for the treatment of Usher syndrome type 2 [ 36 , 41 ].…”
Section: Targeting Nucleic Acidmentioning
confidence: 99%
“…There is extensive pre-clinical and clinical research on the use of ssAONs to correct splicing defects in inherited retinal dystrophies [ 35–37 ]. For example, for Stargardt disease, ssAONs to correct intronic mutations which cause exon elongation or pseudoexons in the ATP-binding cassette transporter type 4 subfamily A, ABCA4 , transcript show promise when tested in various cell models including induced pluripotent stem cell (iPSCs)-derived photoreceptor precursor cells [ 38 , 39 ]. The ssAON, sepofarsen, is under clinical development as a treatment for Leber congenital amaurosis [ 40 ] and an exon skipping ssAON is being investigated for the treatment of Usher syndrome type 2 [ 36 , 41 ].…”
Section: Targeting Nucleic Acidmentioning
confidence: 99%
“…It has only been possible through CRISPR/Cas technology by the induction of single nucleotide substitutions [46,47]. Allele-specific approaches have been successfully tested for intronic variants through splice modulation ASOs that mask the erroneous signalling and given their intronic location and distance to splicing regulatory regions, proper protein synthesis can be recovered [48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with the deep intronic mutation c.2991 + 1655A > G in CEP290, which causes the inherited retinal dystrophy Leber congenital amaurosis, have so far received an intravitreal injection of sepofarsen (ProQR Therapeutics), a 17-mer 2 -O-methylmodified phosphonothioate RNA AON, followed by three monthly top-up injections. Importantly, no serious adverse events have been reported with encouraging signs of improvements to visual acuity at 3 months post treatment [91]. More recently, it was revealed that one patient achieved a sustained response to just a single dose of sepofarsen lasting up to 15 months after treatment [92].…”
Section: Anti-sense Oligonucleotidesmentioning
confidence: 98%